Export Destinations Mapping of Indonesian Tea Products in The International Market - Fikri Aldi Dwi Putro; Widyastutik; Nia Kurniawati Hidayat (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Indonesian tea products have become an export-oriented commodity. However, Indonesian tea products trade performance, particularly the exports, has shown a persistent decline for the last decade (2012–2021). Therefore, this study aims to analyse the competitiveness of Indonesia tea products export as well as map the export destinations for Indonesia tea products. This study employs secondary data regarding tea product export value from UN Comtrade during the 2012–2021 period with analysis using revealed comparative advantage (RCA), export product dynamic (EPD), and X-model potential export product. The RCA results suggest that Indonesian tea products exhibit an overall strong comparative advantage in the international market, albeit still lagging behind India. Additionally, Indonesia also exhibits a strong comparative advantage in all tea products, except tea extract and preparation products. The EPD results show that Indonesia possesses a competitive advantage in packaged black tea, bulk green tea, also tea extract and preparation products. The export destination mapping reveals the 28 potential destinations serving as the focus for Indonesian tea export expansion. These potential destinations are dominated by the non-traditional. Keywords: tea products export, EPD, potential destinations, RCA, X-model potential export product